Problems and prospects of online education in Ukraine (Environment & Health, 2020)
Objective:We identified the main advantages, problems and prospects of distance education in Ukraine.Materials and methods : We developed a questionnaire and proposed to the students and pupils to fill in it with the help of Google form. The questionnaire was completely anonymous. For the convenience of result processing, the respondents were asked to indicate their age, gender and educational institution. Thus, the sample consisted of 323 participants aged 14 - 37 years. 97.8% of them replied that they were studying online at the time of filling the questionnaire, and the majority (64.4%) didn’t have an experience of such an educational format.Results: Most of the respondents were the girls (236 - 73.1%). The average age of the participants was 18 years. In general, the majority of the respondents were satisfied with the online education: 40.6% of the respondents were satisfied with certain comments, about 9% were absolutely satisfied, the rest were either undecided (10.5%) or unsatisfied. 47.7% of the respondents noted lack of motivation to study during online learning. 47.7% of the respondents felt a lack of motivation to study with the transition to distance training, while 38.1% of the respondents didn’t notice such changes. At the same time, 55.7% of the respondents said that learning became more difficult for them. The distance training format requires a high level of self-discipline and self-organization, most respondents managed to complete all the tasks that the educational process required (34.4%). The distance training was easy for 32.2% of the respondents, although they did not always manage to do everything had beenplanned.11.5% of the respondents didn’t have time to complete the tasks and it was quite difficult for them to study. Because the format of distance training in Ukraine is a new experience for both teachers and students, we also highlighted the issues of accessibility and communication between them.Conclusions: In general, the experience of distance education for students and teachers is quite successful, and in the realities of today's world, the online education may take place next to the traditional one in the near future. Therefore, of course, such a convenient tool as distance training should be introduced into practice taking into account the capabilities and features of this format.
Keywords: distance education; online training; pupils; students; advantages; disadvantages